Analisis Pengaruh CAR, NPF, BOPO, dan FDR terhadap ROA (Studi Kasus PT. Bank Muamalat Indonesia Tbk.) - Shafanissa Aulia Zikri; Destian Arshad Darulmalshah Tamara; Muhamad Umar Mai; Ade Ali Nurdin (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
This research is motivated by the existence of problems at Bank Muamalat Indonesia (BMI) over the last few years involving its ability to earn profits, and by looking at the prolonged decline in ROA over the last eight years which shows that BMI as the first Islamic bank in Indonesia has a low ability to generate profits. This study aims to determine the impact of CAR, NPF, BOPO, and FDR on ROA in a BMI case study from 2014 to 2021. Related data to the research issues were collected using literature research methods. The collected data was analyzed using multiple linear regression methods using statistical data processin application tools. The results of this research are the variables CAR, NPF, BOPO, and FDR simultaneously have a significant effect on ROA, partially CAR and FDR have a significant positive effect on ROA, BOPO has a significant negative effect on ROA, and NPF has no significant effect on ROA.